Pretreatment of Real Antibiotic Wastewater by Fenton Process - Elmolla, E. S. (2009)
The feasibility of using Fenton process as a pretreatment for real antibiotic wastewater was evaluated. In addition, the study examined the effect of main parameters (COD/H2O2 molar ratio and H2O2/Fe2+ molar ratio) of the Fenton process on biodegradability (BOD5/COD ratio) improvement and mineralization. The optimum operating conditions for treatment of the antibiotic wastewater was observed to be H2O2/COD molar ratio 2.5 and H2O2/Fe2+ molar ratio 20 (COD/H2O2/Fe2+ molar ratio 1/2.5/0.125) at pH 3 and reaction time 30 min. Under optimum operating conditions, complete degradation of amoxicillin and cloxacillin occurred in one minutes, biodegradability improved from 0.09 to 0.49 ± 0.02 in 30 min, and COD and DOC removal were 62 ± 1% and 37  3 %, respectively in 30 min. The study indicated that the Fenton process can be used as pretreatment for antibiotic degradation, mineralization and biodegradability improvement of antibiotic wastewater containing amoxicillin and cloxacillin.